Educating the future: Serbian healthcare students’ knowledge and attitudes toward urinary incontinence - Dragana Milutinović; Dragana Simin; Marijana Ostoić; Sonja Golubović; Dragana Živković (BMC Medical Education)
Abstract Introduction Urinary incontinence (UI) is a growing global health problem that affects both women and men of all ages and can seriously negatively impact quality of life. Healthcare professionals’ knowledge and attitudes significantly influence UI prevention, diagnosis, and treatment. However, there is a notable lack of research exploring healthcare students’ understanding and perceptions of UI. In many countries, they, as future healthcare professionals, must also have continence care competency before graduation. Therefore, the study aimed to assess the knowledge and attitudes of healthcare students toward UI. Methods The study was designed as an observational, analytical, and comparative cross-sectional with 378 healthcare students in Serbia during the winter semester of the 2023/2024 academic year. A general questionnaire for obtaining sociodemographic data, the Urinary Incontinence Knowledge Scale (UIKS) and the Urinary Incontinence Attitude Scale (UIAS) were used as students’ report measures. Kuder-Richardson Coefficient (K-R 20) showed high reliability of the UIKS at 0.83, while Cronbach’s alpha coefficient was 0.62 for the UIAS. Results The UIKS score was 16.6 ± 3.9/30. Healthcare students achieved the highest score in the domain of knowledge about the impact of UI on quality of life and the lowest in the domain of UI control. There is a significant difference in students’ knowledge level concerning the study program and whether they had a course focusing on UI. The UIAS score was 45.1 ± 4.6/60, indicating a positive attitude to UI. A statistically significant positive but weak correlation was obtained between knowledge and student attitudes about UI. Conclusions The study findings highlight a concerning gap in understanding UI among healthcare students despite their pivotal role as future healthcare professionals and underscore the urgent need for comprehensive educational strategies to bridge the knowledge gap and foster more positive attitudes toward UI and their implementation in clinical practice to improve patient health outcomes.